2017
DOI: 10.1007/s10847-017-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure, electronic, inclusion complex formation behavior and spectral properties of pillarplex

Abstract: systems. The low binding energy, and the physical adsorption of guest molecule and HOMO-LUMO spatial diagram indicates, that the Au and Ag-Pillarplex can be used as reversible host for linear alkanes Complexation of guest engenders frequency shift in the vibrational spectra. Calculated 1 H NMR reveal that guest protons which are closer to the metal sites experience larger shielding possibly due to C-H→LP* metal interaction. The 15 N signal observed for the DAO is nearly identical to that observed for the DAO@ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…68−70 To shed light on host capability of PPX, our group has already studied the electronic structure and the inclusion complex formation behavior of Ag, Au, and Cu metal-centered PPX with the linear chain 1,8-diaminooctane and found that the guest molecule binds ideally within the cavity. 71 Herein, we have explored various gas molecules, such as flue gas, biogas, syngas, corrosive gas, exhaust gas, greenhouse gas, etc. within the Au-PPX cavity and their adsorption and separation behaviors have been studied using multiscale modeling method.…”
Section: Introductionmentioning
confidence: 99%
“…68−70 To shed light on host capability of PPX, our group has already studied the electronic structure and the inclusion complex formation behavior of Ag, Au, and Cu metal-centered PPX with the linear chain 1,8-diaminooctane and found that the guest molecule binds ideally within the cavity. 71 Herein, we have explored various gas molecules, such as flue gas, biogas, syngas, corrosive gas, exhaust gas, greenhouse gas, etc. within the Au-PPX cavity and their adsorption and separation behaviors have been studied using multiscale modeling method.…”
Section: Introductionmentioning
confidence: 99%